Constructing Fiqh and Kalam in the Tafsir of Mujahid bin Jabr - Anwar, Zaeni; Iskhak Nawawi, Mukhamad; Hasmezam, Muhammad Haikal bin; Mohd Zuki, Mohammad A’mmar bin Mohd Naim (STIT Sunan Giri Bima, 2025)
The study of tafsir during the tabi'in period is one of the important phases in the history of the development of the interpretation of the Qur'an. In this period, a number of mufasir emerged who continued the tradition of interpreting the companions with certain patterns and characteristics. One of the central figures was Mujahid bin Jabr, a key disciple of Ibn 'Abbas who was known as an important figure in expanding the horizons of historical interpretation. This research aims to uncover the characteristics of Mujahid bin Jabr's interpretation, especially on fiqh and kalam verses, as well as to trace his contribution to the treasures of tafsir during the tabi'in period. The method used is qualitative with a descriptive-analytical approach through a search of primary and secondary literature. The results of the study show that the interpretation of Mujahid is characterized by the use of strong sanad, short but concise patterns, and a tendency to associate the meaning of verses with aspects of law (fiqh) and theology (kalam). In addition, his interpretation reflects the continuity of the authority of knowledge from Ibn 'Abbas, but still displays a critical power in understanding the text. In conclusion this research confirms that Mujahid bin Jabir's contribution was not only limited to historical interpretation, but also played a significant role in the formation of the framework of fiqh and kalam thought for the generation after him.